Tomato Inoculation With the Endophytic Strain Fusarium solani K Results in Reduced Feeding Damage by the Zoophytophagous Predator Nesidiocoris tenuis - Garantonakis, Nikolaos; Pappas, Maria L.; Varikou, Kyriaki; Skiada, Vasiliki; Broufas, George D.; Kavroulakis, Nektarios; Papadopoulou, Kalliope K. (Frontiers in Ecology and Evolution, 2018)
Belowground symbiosis of plants with beneficial microbes is known to confer resistance to aboveground pests such as herbivorous arthropods and pathogens. Similarly, microbe-induced plant responses may also impact natural enemies of pests via the elicitation of plant defense responses and/or alteration of plant quality and growth. Nesidiocoris tenuis is a zoophytophagous predator and an efficient biological control agent of greenhouse pests. Its usefulness in plant protection is often hindered by its ability to damage plants at high predator population densities or when prey is scarce. In this study, we investigated the effect of Fusarium solani strain K (FsK), an endophytic fungal isolate that colonizes tomato root tissues, on the capability of N. tenuis to cause necrotic rings, an easily discernible symptom, on tomato stems and leaves. We found significantly less necrotic rings formed on FsK-inoculated plants for all tomato cultivars tested. FsK has been previously shown to confer ethylene-mediated tomato resistance to both foliar and root fungal pathogens; thus, the ethylene-insensitive Never ripe (Nr) and epinastic (epi) tomato plant mutant lines were included in our study to assess the role of ethylene in the recorded FsK-mediated plant damage reduction. The jasmonic acid (JA)-biosynthesis tomato mutant def-1 was also used since JA is known to mediate major anti-herbivore plant responses. We show that ethylene and JA are required for FsK to efficiently protect tomato plants from N. tenuis feeding. No necrotic rings were recorded on FsK-inoculated epi plants suggesting that ethylene overproduction may be key to tomato resistance to N. tenuis feeding.